Adult Language Education and Migration Challenging agendas in policy and practice - Simpson, James; Whiteside, Anne (Taylor & Francis, 2015)
Adult Language Education and Migration: Challenging Agendas in Policy and Practice provides a lively and critical examination of policy and practice in language education for adult migrants around the world, showing how opportunities for learning the language of a new country both shape and are shaped by policy moves. Language policies for migrants are often controversial and hotly contested, but at the same time innovative teaching practices are emerging in response to the language learning needs of today's mobile populations. This book: analyses and challenges language education policies relating to adult migrants in nine countries; provides a comparative study with separate chapters on policy and practice in each country; focuses on Australia, Canada, Spain (Catalonia), Finland, France, Ireland, the Netherlands, the UK and the US. Adult Language Education and Migration is essential reading for practitioners, students and researchers working in the area of language education in migration contexts.